Faktor-Faktor Terpenting Yang Mempengaruhi Kepuasan dan Loyalitas Pelanggan Pengguna Jaringan 4G di Denpasar - Silviana Melda Kolo; Gede Sri Darma (Universitas Pendidikan Nasional, 2020)
The purpose of this study is to find out and analyze the effect of product quality and service quality to customer satisfaction, to find out and analyze the effect of quality product and service quality to customer loyalty of Tekomsel’s 4G network user in Denpasar. This study uses primer data in the form of quisioner data distributed to Telkomsel’s 4G network user in Denpasar. By using this random sampling method, then obtained amount of counted 100 samples. The analyis technique used is PLS (Partial Least System (technique). The reserach shows that (1) The product quality has significant influence to the customer’s satisfaction (2) the service quality has significant influnce to the customer’s satisfaction (3) the product quality has significant influence to the customer’s loyalty (4) the service quality has significant influence to the customer’s loyalty (5) the customers satisfacion has significant influence to the customer’s loyalty.